Pengaruh Customer Rating, Live Streaming Selling, dan Customer Review terhadap Impulsive Buying Pembelian Skincare The Originote pada E-Commerce Shopee (Studi pada Mahasiswi PTN di Kota Medan): Penelitian - Vannesia Guiness; Nicholas Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of customer rating, live streaming selling, and customer review on impulsive buying of The Originote skincare products on Shopee e-commerce by female students of public universities in Medan City. This research employs a quantitative method with an associative approach. The population of the study consists of female students from public universities in Medan City. Primary data were collected through questionnaires. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results indicate that customer rating, live streaming selling, and customer review have a significant influence, both partially and simultaneously, on impulsive buying. The coefficient of determination test shows a very strong relationship between customer rating, live streaming selling, and customer review with impulsive buying, with an R value of 0.804. These findings highlight the importance of marketing strategies that leverage rating quality, direct interaction through live streaming, and persuasive customer reviews to stimulate impulsive buying behavior.